PELATIHAN PENYUSUNAN LAPORAN KEUANGAN UNTUK USAHA PEMULA GUNA MENDUKUNG UKM BERDAYA - Oktavera, Rini; Estiasih, Soffia Pudji; Cahyono, Wahyu Eko; Baramadya, Baramadya; Putri, Oktavia Yuliana; Fandy, LM (Jurnal Abdimas Bina Bangsa, 2024)
This community service activity aims to provide counseling to start-up businesses regarding the preparation of Financial Statements. Through this training, novice business activists gain insight that the benefits of making financial reports for SMEs are not only understanding financial management but also offering a comprehensive overview of their performance and positioning for business sustainability decision-making. This community service is located in West Lobeser RT 1, RW 6, Baroon Kel, Baroon Kec, Nganjuk, East Java. The targets in this program are 20 SME owners, mostly red fried onions, carried out on October 8, 2023. Nganjuk Regency is one of the regencies in East Java province, Indonesia. The population is 1,128,593 people (BPS, 2020) with an area of 1,064.33 km. Due to the favorable geographical location, Nganjuk Regency has become a center for shallots, the second largest shallot producer in Indonesia so there are many fried shallot SMEs. The implementation method used was socialization, lectures, counseling, technical guidance, and scheduled mentoring. The stages of the activity include socialization of activities, providing material for preparing financial reports, and monitoring and evaluating the results of training through checking the financial statements prepared by each training participant. The results of the implementation of the activity explained that the level of knowledge and skills of partners in financial report preparation training had increased by 55% from 21.25%. This result shows that the level of understanding and skills of partners is in the good category (76.25%).